Urgical Installation Nurses And Emergency Installation Nurses At Sumedang Regional General Hospital (Indonesian Nursing Science Journal, 2025)
Background: Work stress is psychological pressure or disturbance caused by organizational and personal factors in the work environment. Although work stress can occur in various professions, jobs that involve interaction with other people tend to have higher levels of stress. Nurses as medical personnel who interact most directly with patients play a role in various aspects of the health service system and are vulnerable to experiencing significant work stress.  Design: This type of research is quantitative using a cross sectional approach with a comparative descriptive design, using the DASS-21 questionnaire to determine stress levels.  Setting(s): This research was conducted at the central surgical installation and emergency installation at the Sumedang regional general hospital. Participants: The population in the study were central surgical installation nurses and emergency installation nurses who worked at Sumedang Regional General Hospital, totaling 47 IBS nurses and 38 IGD nurses. With inclusion criteria: 1) Nurses who work in the central surgical installation 2) Nurses who work in the emergency installation 3) Nurses who are willing to be research respondents While the exclusion criteria used: 1) Nurses who are sick when data collectionhe Methods: Data analysis used a non-parametric statistical test, namely the Mann-Whitney Test processed with SPSS. This statistical test was carried out to compare two independent groups based on the median value.  Results: The results of the Mann-Whitney Test statistical test which was carried out to compare the median values ​​of the two groups obtained a p-value (0.001) with a Z value (-3.452) Conclusions: The two groups tested had significant differences.